2018
DOI: 10.1016/j.jshs.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation reduction following an eccentric contraction impairs torque steadiness in the isometric steady-state

Abstract: HighlightsTorque steadiness in the isometric steady-state following an eccentric contraction is impaired compared with a purely isometric contraction.This decrease in torque steadiness is driven by an activation reduction that occurs in the isometric steady-state following an eccentric contraction when torque is matched to that of a purely isometric contraction.When activation was matched between a purely isometric contraction and the isometric steady-state following an eccentric contraction, there was no diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The ankle complex, including the talocrural joint, the subtalar joint, and the inferior tibiofibular joint, is the last joint before contact with the ground and thus represents the final opportunity for adjustments to be made to maintain an upright stance. The crucial role that ankle complex proprioception plays in balance control, daily activities, and mobility has been widely acknowleged 11, 12, 13, 14. Accordingly, scores for ankle-complex proprioception across the human lifespan can provide a normative base against which the proprioceptive status of pediatric and gerontology populations can be compared and, thus, can facilitate the evaluation of interventions designed to improve ankle proprioception.…”
Section: Introductionmentioning
confidence: 99%
“…The ankle complex, including the talocrural joint, the subtalar joint, and the inferior tibiofibular joint, is the last joint before contact with the ground and thus represents the final opportunity for adjustments to be made to maintain an upright stance. The crucial role that ankle complex proprioception plays in balance control, daily activities, and mobility has been widely acknowleged 11, 12, 13, 14. Accordingly, scores for ankle-complex proprioception across the human lifespan can provide a normative base against which the proprioceptive status of pediatric and gerontology populations can be compared and, thus, can facilitate the evaluation of interventions designed to improve ankle proprioception.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported AR and concluded that neuromuscular efficiency following active muscle stretch is increased, which might be explained by enhanced passive forces due to increased titin forces (Oskouei & Herzog, 2005;Altenburg et al, 2008;Seiberl et al, 2012;Joumaa & Herzog, 2013;Jones, Power & Herzog, 2016;Mazara et al, 2018;Paquin & Power, 2018). However, Paquin & Power (2018) also found a rightward shift in the EMGtorque relationship following active stretch compared with fixed-end reference conditions, which indicates that the neuromuscular activation strategy might be altered in the presence of rFE.…”
Section: Introductionmentioning
confidence: 95%
“…AR refers to a reduced muscle activity level needed to maintain a given force/torque following active muscle stretch compared with fixed-end contractions at the same final muscle length. Several studies have reported AR and concluded that neuromuscular efficiency after active muscle stretch is increased, which might in part be explained by enhanced passive forces due to increased titin stiffness (Altenburg et al, 2008; Jones et al, 2016, 2016; Mazara et al, 2018; Oskouei and Herzog, 2005; Paquin and Power, 2018; Seiberl et al, 2012). However, Paquin and Power (2018) also found a rightward shift in the EMG-torque relationship following active stretch compared with fixed-end reference conditions, which indicates that rFE might alter the neuromuscular activation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Following active muscle lengthening, a given submaximal isometric force can be achieved with less neuromuscular activation than before the lengthening stimulus. 2 , 3 , 4 This activation reduction during submaximal contractions ranges from 7%–25% 2 and has been observed across multiple muscles and muscle groups, such as the adductor policis brevis, 3 , 5 , 6 tibialis anterior, 4 , 7 plantar flexors, 8 , 9 , 10 knee extensors, 11 and elbow flexors. 12 Some studies have reported differences in the control of isometric force between conditions that require the subject either to hold a rigid load or to hold an equivalent inertial load in the same anatomical position (i.e., position task) but in free space.…”
Section: Introductionmentioning
confidence: 99%